EFFECT OF PROJECT BASED LEARNING MODEL (PjBL) ON STUDENT LEARNING RESULTS ON THE MATTER OF DIVERSITY OF HABITATIVES - hastya, nirmala; Amrizal (Universitas Negeri Medan, 2025)
This study aims to determine the effect of the Project Based Learning Model on student learning outcomes in ecosystem material in class X IPA SMA Negeri 2 Percut Sei Tuan in the academic year of 2024/2025. The population in this study were all students of class X IPA SMA Negeri 2 Percut Sei Tuan consisting of 9 classes. The sample in this study was 2 classes which were categorized as experimental classes and control classes. The type of research used was Quasi Experiment, the method used in this study was Pre-Experiment, with a Non-equivalent Control Group Design design. The sample used consisted of two classes totaling 60 students who were taken by purposive sampling. The data collection technique used pretest and posttest questions. Based on the data obtained and the data analysis that had been carried out, the value of students' cognitive learning outcomes was obtained. The average pre-test value for the experimental class was 49.167 and the average pre-test value for the control class was 46.833. Furthermore, after being given model treatment in each class, a post-test was given again with the same questions as the pre-test questions, so that the average post-test score for the experimental class was 86.667 and the average score for the control class was 79.5. The data obtained showed that the average score of the experimental class learning outcome test was higher than that of the control class.Then the homogeneity test was conducted and obtained for the Fcount value for the pre-test value is 1.408 and for the Fcount value of the post-test value is 1.520 with the Ftable value of 1.860 with a significance level of 0.05. This shows that Fcount <Ftable, so that the pre-test and post-test data for both classes are said to be homogeneous. Furthermore, for the results of the hypothesis test, the tcount value is 6.2890 and for the ttable value with a significance level of 0.05 is 2.0017. Where tcount is greater than the ttable value (tcount> ttable) which is 6.2890> 2.0017, this shows that H0 is rejected and Ha is accepted, which means that there is an influence of the project based learning model on student learning outcomes in ecosystem material.